Neutrophils in Psoriasis - Chiang, Chih-Chao; Cheng, Wei-Jen; Korinek, Michal; Lin, Cheng-Yu; Hwang, Tsong-Long (Frontiers in Immunology, 2019)
Neutrophils are the most abundant innate immune cells. The pathogenic roles of neutrophils are related to chronic inflammation and autoimmune diseases. Psoriasis is a chronic systemic inflammatory disease affecting approximately 2 to 3% of the world population. The abundant presence of neutrophils in the psoriatic skin lesions serves as a typical histopathologic hallmark of psoriasis. Recent reports indicated that oxidative stress, granular components, and neutrophil extracellular traps from psoriatic neutrophils are related to the initial and maintenance phases of psoriasis. This review provides an overview on the recent (up to 2019) advances in understanding the role of neutrophils in the pathophysiology of psoriasis, including the effects of respiratory burst, degranulation, and neutrophil extracellular trap fromation on psoriatic immunity and the clinical relationships.